La agenda para América del Norte - Gutiérrez Fernández, Gerónimo (Revista Mexicana de Política Exterior, 2022)
In this essay, Gerónimo Gutiérrez reflects on the future of North America from the perspective of the Security and Prosperity Partnershipm of North America (SPPNA). The author highlights the importance of drawing up an agenda that is shared by Mexico, the United States and Canada, the circumstances under which this agenda will evolve, the progress attained and the objectives of the Partnership, which imply greater integration of North America. According to Gutiérrez, the extent to which this integration is achieved will be conditioned by political, economic and social factors in all three countries and their interaction on the international arena. As regards the progress of this integration process —which has directed the consolidation of models of cooperation— the SPPNA represents a new cooperation mechanism that will enable Canada, the United States and Mexico to build on their existing relationships within NAFTA. Gutiérrez concludes that the SPPNA is a realistic and rational cooperation framework that will allow the countries to address the major challenges facing the region in a more effective manner.